2021
DOI: 10.1177/21582440211033251
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Psychological Distance on People’s Willingness to Help Accident Victims: Discrepancies Between Implicit and Explicit Inferences

Abstract: Drawing on construal-level theory, this study explored how a sense of psychological distance from an accident influences people’s willingness to help victims. We conducted a scenario experiment with a sample of 81 Japanese undergraduates. Participants were presented with a short scenario describing an accident that happened on either a distant or a nearby mountain. The results show that the greater the distance perceived by participants from the accident, the more likely they were to infer negative traits abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…For example, recent study ( Holbrook et al, 2022 ) found that although Korean and American participants showed similar moral parochialism in moral condemnation, Korean participants were more likely than American ones to attribute transgressive behavior to situational and contextual factors. Moreover, Taniguchi and Ikegami (2021) found that participants were more likely to apply implicit attribution to a victim’ s internal disposition (carelessness) from an accident that occurred at a distant relative to the near location, which is consistent with the CLT theory. These evidence suggested that implicit attributions (such as spontaneous justice inferences) and explicit moral condemnation might be two different processes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For example, recent study ( Holbrook et al, 2022 ) found that although Korean and American participants showed similar moral parochialism in moral condemnation, Korean participants were more likely than American ones to attribute transgressive behavior to situational and contextual factors. Moreover, Taniguchi and Ikegami (2021) found that participants were more likely to apply implicit attribution to a victim’ s internal disposition (carelessness) from an accident that occurred at a distant relative to the near location, which is consistent with the CLT theory. These evidence suggested that implicit attributions (such as spontaneous justice inferences) and explicit moral condemnation might be two different processes.…”
Section: Discussionsupporting
confidence: 78%
“…Second, the present study also extends the literature on CLT and spontaneous social inference. Previous research has found that psychological distance affects spontaneous trait inferences (STIs, Rim et al, 2009;Taniguchi and Ikegami, 2021). It should be noted that STIs reflect spontaneously dispositional attribution processes made about the actor (Trait A is a property of actor X).…”
Section: Discussionmentioning
confidence: 98%
“…Perceptions of the cause and effects are often closely intertwined, and parallel literature on correspondence bias (Gilbert, 1989) has addressed the linkage between psychological distance and attribution judgments (Mentovich et al., 2016; Taniguchi & Ikegami, 2021). While this line of work has examined how the cause of psychologically distant versus proximal behaviors is differently attributed, causal attribution frames may also shape to what extent people feel close to the issue or behavior described in the message.…”
Section: Causal Attribution Frames On Transboundary Riskmentioning
confidence: 99%